Political Party and People’s Suffrage in Electoral Process - Tomu A. Pasaribu; John Pieris; Manotar Tampubolon (Polit Journal Scientific Journal of Politics, 2022)
The purpose of this research is to determine political parties' positions on people's constitutional rights from the standpoint of justice. The author focuses on the role of political parties in selecting representatives or leaders in accordance with the constitutional rights guaranteed by the constitution. The research question is: What is the position of political parties on people's constitutional rights in terms of justice? Is the fulfillment of the people's constitutional rights by the Leader elected in a General Election in accordance with the aspect of justice? As trustworthy resources, the author employs secondary data in the form of documents gathered through library research. This study highlights the positions of political parties that disregard the constitutional rights of the people, which are in conflict with the rights of the people as the owners of the right to be elected and vote.